"Everything is provided free, but they are still hesitant to access healthcare services": why does the indigenous community in Attapadi, Kerala continue to experience poor access to healthcare? - Mathew Sunil George; Rachel Davey; Itismita Mohanty; Penney Upton (BMC, 2020)
Abstract Background Inequity in access to healthcare services is a constant concern. While advances in healthcare have progressed in the last several decades, thereby significantly improving the prevention and treatment of disease, these benefits have not been shared equally. Excluded communities such as Indigenous communities typically face a lack of access to healthcare services that others do not. This study seeks to understand why the indigenous communities in Attapadi continue to experience poor access to healthcare in spite of both financial protection and adequate coverage of health services. Methods Ethnographic fieldwork was carried out among the various stakeholders living in Attapadi. A total of 47 in-depth interviews and 6 focus group discussions were conducted amongst the indigenous community, the healthcare providers and key informants. The data was coded utilising a reflexive and inductive approach leading to the development of the key categories and themes. Results The health system provided a comprehensive financial protection package in addition to a host of healthcare facilities for the indigenous communities to avail services. In spite of this, they resisted attempts by the health system to improve their access. The failure to provide culturally respectful care, the discrimination of the community at healthcare facilities, the centralisation of the delivery of services as well as the lack of power on the part of the indigenous community to negotiate with the health system for services that were less disruptive for their lives were identified as the barriers to improving healthcare access. The existing power differentials between the community and the health system stakeholders also ensured that meaningful involvement of the community in the local health system did not occur. Conclusion Improving access to health care for indigenous communities would require UHC interventions to be culturally safe, locally relevant and promote active involvement of the community at all stages of the intervention. Continuing structural power imbalances that affect access to resources and prevent meaningful involvement of indigenous communities also need to be addressed.